Virtual reality vs traditional education: Is there any advantage in human neuroanatomy teaching?. (July 2021) - Lopez, Mildred; Arriaga, José Gerardo Carrillo; Nigenda Álvarez, Juan Pablo; González, Ricardo Treviño; Elizondo-Leal, José Antonio; Valdez-García, Jorge E.; Carrión, Belinda
Abstract: Traditional medical education still focuses on masterclasses and the presentation of the rarest and hardest-to-diagnose diseases, hardly observed in a professional context. Technologies such as virtual reality can enrich educational environments to visualize intricate structures and provide assessment and timely feedback. This study's objective was to analyze whether there is any advantage of teaching with virtual reality vs. traditional education. The quantitative and descriptive approach considered a sample of 120 students in the human neuroanatomy class. They were part of two groups: the control group participated in a traditional class, experimental in a virtual reality session. Their performance was cataloged in: 1-insufficient, 2-under development, and 3-competent. A significant difference was found as the control group obtained a mean of 1.63, while the experimental 2.28. Students who used virtual reality seem to demonstrate better performance in identifying structures and describing the functional implications. Graphical abstract: Image, graphical abstract